The Geospatial and Temporal Dynamics of Agricultural Residue Burning: A Regional Study of Haryana, 2017-2023 - Devender Sindhu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The Green Revolution has resulted in an unprecedented increase in Punjab and Haryana’s agricultural production. The Green Revolution’s impact extended beyond agricultural production, altering the cropping pattern of a semi-arid state such as Haryana, leading to the replacement of coarse grain crops with rice and wheat. Improved seeds and irrigation facilities contributed significantly to this crop pattern change. The minimum support price and available market for wheat and rice attracted farmers to grow rice and wheat in more and more areas. This sequential cropping patten of rice and wheat gave rise to the tradition of agricultural residues burning by farmers, which is currently causing severe air pollution in the months of November and December in northern India.By restricting the paddy crop cropping time through the Haryana Preservation of Subsoil Water Act, 2009, residues are being burned in the state. The present study focuses on identifying temporal pattern, trend, and hotspot of Haryana state where agricultural residues burning has been ongoing for years. This study utilized data from the MCD64A1 Version 6 Burned Area data product from the Terra and Aqua satellites. Satellite data from 2017 to 2023for the months of October and November, have been selected which correspond to the period after paddy crops and before wheat crops. District- and sub divisional level hotspots of agricultural residues have been identified using QGIS software.